Contester par projets. Le cas des monnaies locales associatives - Jérôme Blanc (Revue de la Régulation)
Associative currencies that circulate locally and for market activities have been developing in France mainly since 2010. They are built on a contestation oriented toward an alternative economy and they are shaped as projects aiming at acting on reality. Consequently, they operate a convergence between criticism and initiative. This text analyses how the use of the category of project by the activists may generate a feedback on the very scope of contestation. The text, thus, starts with an analysis of the criticism or contestation that drives associative currencies initiatives. Then, it shows why these initiatives take a project the form and stresses the possible contradiction between project and contestation of neoliberal capitalism. It outlines the category of “world of solidarity projects” in order to take account of the specific kind of projects that are associative local currencies. An insight into a particular associative currency initiative, seen through the lenses of project management, helps identify how the latter leads to shifts in the project itself. This leads to ponder the capacity of such projects to turn their alternative dimension concrete and, consequently, to contribute to the desired social transformation.